2016
DOI: 10.1093/ehjqcco/qcw004
|View full text |Cite
|
Sign up to set email alerts
|

Using big data from health records from four countries to evaluate chronic disease outcomes: a study in 114 364 survivors of myocardial infarction

Abstract: AimsTo assess the international validity of using hospital record data to compare long-term outcomes in heart attack survivors.Methods and resultsWe used samples of national, ongoing, unselected record sources to assess three outcomes: cause death; a composite of myocardial infarction (MI), stroke, and all-cause death; and hospitalized bleeding. Patients aged 65 years and older entered the study 1 year following the most recent discharge for acute MI in 2002–11 [n = 54 841 (Sweden), 53 909 (USA), 4653 (England… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
91
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(103 citation statements)
references
References 54 publications
7
91
1
4
Order By: Relevance
“…We observed a high rate of MI and IS recurrence in the first year of survival after an MI or IS (7.7% and 6.7%, respectively), and the risk of recurrence persisted and continued to increase for up to 6 years of follow‐up (14.3% and 13.4%, respectively). These findings confirm results from other retrospective observational studies, in which the risk of recurrent events was highest in the first year but remained elevated in subsequent years . Moreover, many patients in this Medicare sample experienced multiple recurrent events (11.6 and 10.2 events per 100 patient‐years for MI and IS, respectively, in the 2012 cohort).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We observed a high rate of MI and IS recurrence in the first year of survival after an MI or IS (7.7% and 6.7%, respectively), and the risk of recurrence persisted and continued to increase for up to 6 years of follow‐up (14.3% and 13.4%, respectively). These findings confirm results from other retrospective observational studies, in which the risk of recurrent events was highest in the first year but remained elevated in subsequent years . Moreover, many patients in this Medicare sample experienced multiple recurrent events (11.6 and 10.2 events per 100 patient‐years for MI and IS, respectively, in the 2012 cohort).…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of comorbidities such as hypertension and diabetes, was high in the study population, and as shown in other studies, diabetes is a significant risk factor for recurrent events . In the Hoorn cohort study, the incidence of a recurrent cardiovascular event during approximately 4 years of follow‐up was 60% higher for individuals with diabetes compared with those without, and higher glycated hemoglobin was one of the predictive risk factors for a recurrent event .…”
Section: Discussionsupporting
confidence: 62%
“…However, the large proportionate difference in outcome rates between STEMI and NSTEMI in this study would not likely be accounted for by the different treatment rates . The relative contribution of the cardiovascular risk factors and comorbidities to outcome rates and costs are consistent with previous shorter term studies that show that prior MIs are strongly associated with recurrent MI and cardiovascular death than with all‐cause mortality, while other comorbidities, including heart failure, diabetes, and renal disease, are strongly associated with all‐cause mortality . This continuity of risk patterns may indicate that the same mechanisms that drive short‐term post‐MI risk also drive risk in this more robust, survivor population.…”
Section: Discussionsupporting
confidence: 84%
“…In this respect, biomaterials stored in centralized biobanks need to be linked to rich clinical information of the patients' course of disease. Future biomedical insights can only be achieved if those biobanks are connected as large networks which are able to provide sufficient data even for very small disease subgroups [9,64]. Predictive models are typically trained in data-driven procedures.…”
Section: Data Sciencementioning
confidence: 99%